Public-private partnership delivers climate advisory to 26,064 crop and fish farmers in Myanmar - Khaung, Ye; McGrath, Quyen; Le, Tam Thi; Swaans, Cornelis (2025)
In 2024, 26,064 crop and fish farmers in Myanmar benefitted from climate advisory. Through a unique partnership led by Village Link Company Ltd and the Alliance of Bioversity International and CIAT, farmers received monthly and weekly advisories and alerts based on climate/weather forecasts and decision trees through the Htwet Toe digital application to reduce risks. Both crop and fish farmers received digital literacy training, with fish farmers being identified and recommended for microfinance loans.